2005
DOI: 10.1542/peds.2004-1238
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Postnatal Systemic Corticosteroids on Mortality and Cerebral Palsy in Preterm Infants: Effect Modification by Risk for Chronic Lung Disease

Abstract: The effect of postnatal corticosteroids on the combined outcome of death or CP varies with the level of risk for CLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
187
2
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(204 citation statements)
references
References 39 publications
3
187
2
7
Order By: Relevance
“…12 Independent of steroid exposure, the presence of BPD itself confers a risk of adverse neurodevelopment and this risk is amplified in those with more severe BPD. 15 Thus, steroid administration in some infants may improve overall outcomes if BPD rates or severity are decreased. In an elegant meta-analysis by Doyle et al, it appeared that when risk of chronic lung disease rose above 65%, steroid use significantly reduced the risk of death or cerebral palsy, whereas the opposite effect was seen when chronic lung disease risk was less than 35%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Independent of steroid exposure, the presence of BPD itself confers a risk of adverse neurodevelopment and this risk is amplified in those with more severe BPD. 15 Thus, steroid administration in some infants may improve overall outcomes if BPD rates or severity are decreased. In an elegant meta-analysis by Doyle et al, it appeared that when risk of chronic lung disease rose above 65%, steroid use significantly reduced the risk of death or cerebral palsy, whereas the opposite effect was seen when chronic lung disease risk was less than 35%.…”
Section: Discussionmentioning
confidence: 99%
“…In high-risk cohorts with sBPD such as described here, the point at which the risk of steroid use may outweigh benefit urgently warrants further investigation so that this therapy can be used appropriately and with effectiveness. 15,27,28 This analysis also starts to define the frequency of exposure to opiates and/or BZs in the most preterm infants in this cohort, despite limited data supporting their safety or benefit in preterm infants. 29,30 Also, both human and animal models have demonstrated an adverse association with future neurodevelopment with the use of these medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 The lack of sustained clinical benefits from late postnatal therapeutic interventions and the undesirable harmful effects of post-natal corticosteroids have fueled interest in seeking early biological markers useful in targeting therapeutic interventions aimed at promoting long-term pulmonary and neurodevelopmental benefits. 4,5 Two previous studies reported genetic influences in the etiology of BPD. The first was a family study by Parker et al, which showed a higher concordance for BPD within pairs of affected siblings.…”
Section: Introductionmentioning
confidence: 99%
“…The American Academy of Pediatrics and the Canadian Pediatric Society recently published guidelines for the use of postnatal steroid treatment in preterm infants (1). With regard to the long-term effects on the brain, studies have documented adverse outcomes, including cerebral palsy and delayed and abnormal neurological development (5,6,12,18,41). The short-term cardiovascular effects after neonatal dexamethasone treatment include hypertension and hypertrophic cardiomyopathy.…”
mentioning
confidence: 99%